On q-Laplace type integral operators and their applications - UÇAR, FARUK (TAYLOR & FRANCIS LTD, 2012)
In this work, two q-Laplace type integral transforms called L-q(2)-transform and L-q(2)-transform are introduced. Some properties of q-analogues of the L-2-transform are given, and several relationships between them are studied. Moreover, we show that the new Laplace type q-integral transforms may be regarded as q-extension of the L-2-transform. Some illustrative examples are also given.
Keywords: q-calculus; Jackson integral; q-Laplace transform; q-gamma function; the L-q(2)-transform; L-q(2)-transform